Reduced developmental competence of immature, in-vitro matured and postovulatory aged mouse oocytes following IVF and ICSI - Trounson Alan; Lacham-Kaplan Orly (BMC, 2008)
Abstract Background The present study highlights basic physiological differences associated with oocyte maturation and ageing. The study explores the fertilizing capacity and resistance to injury of mouse oocytes at different stages of maturation and ageing following IVF and ICSI. Also, the study examines the developmental competence of embryos obtained from these oocytes. The outcome of the study supports views that the mouse can be a model for human IVF suggesting that utilizing in-vitro matured and failed fertilized oocytes to produce embryos mainly when limited number of oocytes is retrieved in a specific cycle, should be carefully considered. Methods Hybrid strain mouse oocytes were inseminated by in-vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Oocytes groups that were used were germinal vesicle (GV) in-vitro matured metaphase II (IVM-MII), freshly ovulated MII (OV-MII), 13 hrs in-vitro aged MII (13 hrs-MII) and 24 hrs in-vitro aged MII (24 hrs-MII). Fertilization and embryo development to the blastocyst stage were monitored up to 5 days in culture for IVF and ICSI zygotes. Sperm head decondensation and pronuclear formation were examined up to 9 hrs in oocytes following ICSI. Apoptotic events in blocked embryos were examined using the TUNNEL assay. Differences between females for the number and quality of GV and OV-MII oocytes were examined by ANOVA analyses. Differences in survival after ICSI, fertilization by IVF and ICSI and embryo development were analysed by Chi-square test with Yates correction. Results No differences in number and quality of oocytes were identified between females. The findings suggest that inability of GV oocytes to participate in fertilization and embryo development initiates primarily from their inability to support initial post fertilization events such as sperm decondensation and pronuclei formation. These events occur in all MII oocytes in similar rates (87-98% for IVF and ICSI). Following ICSI, pronuclei appeared in IVM and freshly ovulated oocytes by 8-9 hrs after insemination. In comparison, pronuclei appeared in 13 hrs aged oocytes by 4-5 hrs. Significantly higher proportions (P < 0.001) of blastocysts resulted from OV-MII oocytes than the other groups examined with 75% and 71% for IVF and ICSI, respectively. The 13 hrs-MII oocytes resulted in 47 and 40% blastocysts, while IVM-MII and 24 hrs-MII oocytes resulted in 38% and 0% blastocysts from IVF and 5% and 5% from ICSI, respectively. In addition, anucleate cells and DNA fragments were observed in retarded embryos derived from IVM and aged oocytes, however, apoptotic events were similar for all groups. Conclusion The data suggests that the use of oocytes other than freshly ovulated MII should be carefully considered for assisted reproduction.